Effect of vortex deflection on vortex-rotor interaction - Wall, B.G. van der (My University, 2019)
Vortex-rotor interaction has been studied mostly with “rigid” straight-line vortices (longitudinal, lateral and or-thogonal to the rotor disk). Vortex deformation during encounter with the rotor was only addressed by means of CFD codes. This paper investigates the interaction by a simplified vortex deflection model, where the in-teracting vortex is convected in parallel to the wake tube of the rotor once it penetrates the rotor disk. The consequences on rotor controls required to keep the trim constant are compared to former results obtained with a rigid (undeflected) vortex model.